Ontogenetic transitions, biomechanical trade-offs and macroevolution of scyphozoan medusae swimming patterns - von Montfort, Guilherme M.; Costello, John H.; Colin, Sean P.; Morandini, André C.; Migotto, Alvaro E.; Maronna, Maximiliano M. [UNESP]; Reginato, Marcelo; Miyake, Hiroshi; Nagata, Renato M. (Springer Nature, 2023)
Ephyrae, the early stages of scyphozoan jellyfish, possess a conserved morphology among species. However, ontogenetic transitions lead to morphologically different shapes among scyphozoan lineages, with important consequences for swimming biomechanics, bioenergetics and ecology. We used high-speed imaging to analyse biomechanical and kinematic variables of swimming in 17 species of Scyphozoa (1 Coronatae, 8 “Semaeostomeae” and 8 Rhizostomeae) at different developmental stages. Swimming kinematics of early ephyrae were similar, in general, but differences related to major lineages emerged through development. Rhizostomeae medusae have more prolate bells, shorter pulse cycles and higher swimming performances. Medusae of “Semaeostomeae”, in turn, have more variable bell shapes and most species had lower swimming performances. Despite these differences, both groups travelled the same distance per pulse suggesting that each pulse is hydrodynamically similar. Therefore, higher swimming velocities are achieved in species with higher pulsation frequencies. Our results suggest that medusae of Rhizostomeae and “Semaeostomeae” have evolved bell kinematics with different optimized traits, rhizostomes optimize rapid fluid processing, through faster pulsations, while “semaeostomes” optimize swimming efficiency, through longer interpulse intervals that enhance mechanisms of passive energy recapture.